Reaction mechanisms of methylidine radical theoretically with trans- and cis-hidroximethylene - Tho, Nguyen Huu; Minh Hue, Nguyen Thi (Vietnam Journal of Chemistry, 2012)
The reaction mechanisms of methylidene radical (CH) with trans- and cis-hydroximethylene have been studied theoretically by means Density Functional Theory (DFT) calculations using BHandHLYP method with the basis set aug-cc-pvdz and aug-cc-pvtz. Our present results indicate that pre reaction complexes formed without activation energy barriers at the initial stage of the both reaction mechanisms. The possible pathways for the formation of 7 products such as CH2 + HCO, CH3 + CO, H2CCO +H, H2 + CCHO, C2H + H2O, HCCOH + H and C2H2 + OH) has been discussed in detail.